2001
DOI: 10.1001/archpsyc.58.5.466
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Somal Size of Deep Layer 3 Pyramidal Neurons in the Prefrontal Cortex of Subjects With Schizophrenia

Abstract: These findings independently replicate previous reports of decreased somal size in the PFC in schizophrenia. The reduction in size of deep layer 3 pyramidal neurons is consistent with abnormalities in thalamocortical and corticocortical circuitry, suggesting that disruption of these circuits may contribute to cognitive abnormalities in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
143
2
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(160 citation statements)
references
References 56 publications
12
143
2
3
Order By: Relevance
“…This has led to studies having more subjects and better matching for tissue pH, postmortem interval, age, and sex (Webster, 2006). Another approach is to utilize dyads or triads of matched subjects, increasing the power to detect an effect (Glantz and Lewis, 1997;Pierri et al, 2001). The field is shifting away from studies with o10 subjects per group, and the increased sample sizes accord increased statistical power to detect significant changes with smaller effect sizes (Carter et al, 2007).…”
Section: Sample Size and Study Designmentioning
confidence: 99%
“…This has led to studies having more subjects and better matching for tissue pH, postmortem interval, age, and sex (Webster, 2006). Another approach is to utilize dyads or triads of matched subjects, increasing the power to detect an effect (Glantz and Lewis, 1997;Pierri et al, 2001). The field is shifting away from studies with o10 subjects per group, and the increased sample sizes accord increased statistical power to detect significant changes with smaller effect sizes (Carter et al, 2007).…”
Section: Sample Size and Study Designmentioning
confidence: 99%
“…Since COMT proteins have been detected exclusively in the neuropil of the cerebral cortex (Kaplan et al, 1979;Karhunen et al, 1994;Lundstrom et al, 1995) and neurons are the primary cell population producing COMT mRNA, it is reasonable to assume that COMT is located at dendrites and/or spines in the prefrontal cortex (Matsumoto et al, 2003). Interestingly, the prefrontal cortex of patients with schizophrenia has been reported to show reduced cortical neuropil, particularly in layer II , and decreased somal size of pyramidal neurons in layer III (Pierri et al, 2001;Rajkowska et al, 1998), both of which could be related to reduced dendritic arborization. Thus, lower levels of pyramidal COMT mRNA in these external cortical layers may reflect this putative reduction of dendrites and/or spines, where COMT protein is presumably located, and may implicate catecholaminergic synapses as part of this process.…”
Section: Discussionmentioning
confidence: 99%
“…Cytoarchitectural studies have found evidence for an increase in neuronal density, 9 decrease in neuronal size, 10,11 reduced pyramidal neuron dendritic field 12,13 and decreased dendritic spine density 14,15 with similar reductions in neuronal size observed in BPD. 16 Efforts to determine the neurochemical and molecular basis for these cellular alterations have revealed abnormalities in neurotransmission, signal transduction, inhibitory interneuron function and glial cells.…”
Section: Introductionmentioning
confidence: 92%